Phytochemical investigation and assessment of the anti-inflammatory activity of four Heracleum taxa growing in Turkey - Kurtul, Ekin; Küpeli Akkol, Esra; Karpuz Ağören, Büşra; Yaylacı, Büşra; Bahadır Acıkara, Özlem; Sobarzo-Sánchez, Eduardo (Frontiers in Pharmacology, 2025)
IntroductionHeracleum L. has been known as “hogweed” and used for inflammatory diseases, including fever, enteritis, and bronchitis, for many years worldwide. The Heracleum genus is also prominently recognized for its high content of coumarins, which are considered a significant group of natural compounds known for their noteworthy anti-inflammatory properties.MethodsThe present study evaluated the anti-inflammatory activity of dichloromethane and methanolic extracts from H. paphlagonicum, H. sphondylium subsp. ternatum, H. sphondylium subsp. elegans, and H. sphondylium subsp. cyclocarpum (100 mg/kg), which have not been previously investigated for their anti-inflammatory properties. Inflammation models induced by carrageenan, prostaglandin E2, and serotonin were employed to evaluate anti-inflammatory activity, using indomethacin (10 mg/kg) as the reference standard. Statistical differences between treatment and control groups were evaluated using ANOVA with Student-Newman-Keuls post-hoc tests. Additionally, the coumarin contents of the extracts were quantified as mg/g by high-performance liquid chromatography.Results and discussionH. sphondylium subsp. cyclocarpum roots displayed the highest inhibition for carrageenan, prostaglandin E2, and serotonin-induced hind paw edema, with inhibition ranges of 22.8%–36.9%, 5.4%–35.7%, and 3.9%–17.9%, respectively, while the inhibition ranges for indomethacin were 12.8%–44.3%, 2.7%–41.3%, and 7.1%–30.6%, respectively. The highest bergapten and imperatorin quantities were found in H. sphondylium subsp. cyclocarpum roots (0.49% and 0.14%) and in H. sphondylium subsp. elegans roots, which had the highest xanthotoxin level (0.06%). Angelicin was detected in H. paphlagonicum, H. sphondylium subsp. elegans, and H. sphondylium subsp. cyclocarpum roots at concentrations of 0.04%, 0.04%, and 0.02%, respectively. The correlation between the highest inhibitory activity observed in H. sphondylium subsp. cyclocarpum roots and the elevated levels of coumarins, particularly bergapten and imperatorin, suggests a potential link between coumarin concentration and anti-inflammatory effects. Additionally, our findings support the traditional use of this genus for treating inflammatory disorders. Further investigations are necessary to identify the active compounds and elucidate the mechanisms of action of these plants, potentially leading to the discovery of novel therapeutic options for the treatment of inflammation.